Low-level aerial survey techniques - Grimsdell, J.J.R.; Westley, S. (International Livestock Centre for Africa, 1981)
Presents workshop papers & discussion summaries on the development of low-level aerial survey techniques and presents applications to livestock, wildlife and land-use surveys. Reviews survey designs and sampling procedures as well as problems of bias, levels, from ground survey to satellite imagery; along w. recommendations for further research and cooperation.